The Impact of Effective Governance and Regulatory Quality on Financial Development Under Economic Conditions of the Mena Countries - SARHANGI, KAMRAN; NIYA, MOHAMMAD JAVAD MOHAGHEGH; AMIRI, MAGHSOUD; SARGOLZAEI, MOSTAFA; SARVOLIA, MOHAMMAD HASSAN EBRAHIMI (The journal of contemporary issues in business and government, 2021)
The present study uses the Systematic Generalized Method of Moment's (SGMM) model to investigate the effects of effective governance and regulatory quality on financial development in the economic conditions of the Mena countries during the period 2002-2009. The results of the study show a positive relationship between the role or rule of law (RL) and economic growth (GDP) with financial development (FD). The variables of regulatory quality (RO), government budget deficit (BD), government effectiveness (GE) and financial crisis (FC) are negative. The negative sign of regulatory quality, government effectiveness and budget deficit for the MENA countries can be justified as follows; The more accountable and efficient the government in a country, the greater the political stability, the lower the additional regulations and costs, the more extensive the rule of law, the smaller the government effectiveness, and the more restricted the corruption, the greater the financial development requiring the more attention of government and authorities in accountability, compliance of rules and regulatory quality. Also the positive variable of the dependent variable lag; the financial development Index shows the countries' attention to the financial development issue and the use of strategies and infrastructure to increase financial development based on financial liberalization indicators over time, which requires much attention from government authorities.